The State and Constitutional Responsibility in Ensuring the Security of Citizens from Intimidation by Thuggery - Yunus, Nur Rohim; Siagian, Amrizal; Raihani, Fina (STAATSRECHT: Indonesian Constitutional Law Journal, 2024)
The phenomenon of gangsterism in Indonesia has developed into a form of non-state violence that threatens social order and the sense of security of the community. Gangs are not only detrimental to individuals, but also create an atmosphere of fear and distrust of law enforcement officers. In this context, the state has a constitutional obligation to protect the fundamental rights of citizens, including the right to a sense of security as guaranteed in Article 28G paragraph (1) and Article 30 paragraph (4) of the 1945 Constitution. This study specifically aims to examine the extent to which the state carries out its constitutional responsibilities in ensuring the security of citizens from intimidatory actions by gangster groups. The research method used is qualitative, with literature study techniques and legal-political analysis. Data were obtained through a study of scientific journals, laws and regulations, and government policy documentation related to overcoming gangsterism. The study results show that although there is a relatively strong legal framework in overcoming gangsterism, its implementation still faces serious challenges. Weak law enforcement, the dominance of a repressive approach without structural solutions, and the lack of rights-based social protection cause the practice of gangsterism to continue. Therefore, this study recommends integrating a firm legal approach and inclusive social policies as an effective strategy to realize just citizen security. The state must act actively and reasonably in carrying out its constitutional mandate to ensure a sense of security for all its citizens.